(untitled) (Revista de Ciências Agroveterinárias, 2024)
Small ruminant husbandry is an important source of subsistence and income for family farmers, contributing to food security and socioeconomic development. To increase the production of these animals while aiming for low feeding costs, it is necessary to resort to different food alternatives that not only reduce expenses but also provide the animals with higher nutrient consumption and utilization. In this context, mesocarp and babassu oil emerge as dietary alternatives, which are generally considered nutritious sources, improving productive performance and reducing metabolic diseases caused by high grain concentration in the diet. The objective of this literature review is to survey the consumption and digestibility of nutrients in small ruminants fed with babassu oil and mesocarp in the North and Northeast regions of Brazil. The selected articles for this review were published in databases from 2013 to 2023, using the following inclusion criteria: babassu oil, babassu mesocarp, alternative feeding, lambs nutrition, intake, and digestibility of nutrients. The studies indicate that babassu oil and mesocarp can be used in small ruminant feeding, resulting in significant gains in nutrient consumption and digestibility. However, there are restrictions regarding the use of these alternative feeds in the diet, with the appropriate quantity for mesocarp being between 10% to 10.5%, and for babassu oil, up to 7%.